The effect of crosswinds on ride comfort in high speed trains running on curves (2015)
The effect of crosswinds on the risk of railway vehicles overturning has been a major issue ever since manufacturers began to produce lighter vehicles that run at high speeds. However, ride comfort can also be influenced by crosswinds, and this effect has not been thoroughly analyzed. This article describes the effect of crosswinds on ride comfort in high speed trains when running on curves and for several wind velocities under a Chinese hat wind scenario, which is the scenario recommended by the standard. Simulation results show that the combination of crosswinds and the added stiffness of the lateral bumpstop on the secondary suspension can become a significant source of instability, leading to flange-to-flange contact and greatly jeopardizing ride comfort. Moreover, this comfort problem is an issue even when the wheel unloading ratio is well below the standard’s limits and vehicle safety can be guaranteed.